1993
DOI: 10.1007/bf01740905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of stimulation of human natural killer cytotoxicity by arabinogalactan fromLarix occidentalis

Abstract: Cultures of human peripheral blood mononuclear cells (PBMC) as well as cultures of preseparated peripheral non-adherent cells (PNAC) and monocytes showed enhancement of natural killer (NK) cytotoxicity against K562 tumor cells when pretreated with arabinogalactan from Larix occidentalis for 48-72 h. Lack of enhanced responses of PBMC (37% of donors) did not necessarily mean that PNAC and monocyte cultures were also non-responsive to arabinogalactan treatment. Moreover, PBMC, PNAC and monocytes of individual do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Arabinogalactans are found in several microbial systems and many plants, mostly in a glycopeptide form, bound to threonine, proline or serine and then to a peptide chain (arabinogalactan protein (AGP)) [34]. There is much evidence that arabinogalactans can interfere in the immune response [29,31], examples being those isolated from Echinacea purpurea, Baptisia tinctoria, Thuja occidentalis [29], Angelica acutiloba [35], and Curcuma longa [30]. Saima et al [27], have isolated an anti-tumor acidic polysaccharide from the fruit of Feronia limonia (Linn.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabinogalactans are found in several microbial systems and many plants, mostly in a glycopeptide form, bound to threonine, proline or serine and then to a peptide chain (arabinogalactan protein (AGP)) [34]. There is much evidence that arabinogalactans can interfere in the immune response [29,31], examples being those isolated from Echinacea purpurea, Baptisia tinctoria, Thuja occidentalis [29], Angelica acutiloba [35], and Curcuma longa [30]. Saima et al [27], have isolated an anti-tumor acidic polysaccharide from the fruit of Feronia limonia (Linn.).…”
Section: Introductionmentioning
confidence: 99%
“…A class that has been receiving attention is the arabinogalactan [28][29][30][31][32][33][34], which consists of heavily branched highmolecular weight polysaccharides (mw 10,000-120,000) [31]. Arabinogalactans are found in several microbial systems and many plants, mostly in a glycopeptide form, bound to threonine, proline or serine and then to a peptide chain (arabinogalactan protein (AGP)) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our data are in line with in vitro and animal studies that showed various immunomodulating effects of arabinogalactan on markers of the innate as well as adaptive immunity. Hence, in response to arabinogalactan, human peripheral blood mononuclear cells (PBMC) and their subpopulations have been shown to release pro-inflammatory cytokines which stimulated NK cytotoxicity 11 . Moreover, larch arabinogalactan activated lymphocytes and macrophages in vitro which provokes a variety of cellular response including enhanced phagocytosis, oxidative burst and the modulation of cytokine production 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Arabinogalactan from larch was demonstrated to stimulate the innate immunity by increasing the NK cell cytotoxicity and the phagocytic capacity of macrophages and monocytes mediated by pro-inflammatory cytokines [9][10][11][12] . Udani et al 13 suggested that arabinogalactan acts in a more specific manner on the adaptive immunity, as shown in the increase in antibody response to the pneumonia vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that some complex of Galactose, Arabinose and/or Gulucose might be novel ligands for TLR2 or TLR4. Indeed, arabinogalactan, lipoarabinomannan and galactomannan were reported as stimulator of DCs [49][50][51]. Previously, it is reported that arabinogalactan have an adjuvant activity for human PBMC.…”
Section: Discussionmentioning
confidence: 99%